The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12903-022-02220-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of botulinum toxin A injection on the lateral pterygoid muscle in patients with a painful temporomandibular joint click: a randomized clinical trial study

Abstract: Background Temporomandibular disorder (TMD) is the main cause of non-dental pain in orofacial area. The most common symptoms of TMD are joint pain, joint sound and limitation of jaw function. Botulinum toxin (BTX) injection is considered a potential treatment for TMD due to its pain-relieving properties and its ability to reduce muscle activity. Most of the studies are case series and further investigations are required to prove the efficacy of this treatment modality. Thus, in this study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…These results would agree with those obtained by Bakke et al [ 57 ], who, by BTX-A injections into the lateral pterygoid muscle, temporarily reduced the muscle action, but the clicking was permanently eliminated and did not reappear during the 1-year observation period, obtaining a small but clear positional improvement in the disc–condyle relationship. Similarly, other studies [ 58 , 59 , 60 ] with BTX-A injections into the lateral pterygoid muscle reported benefits on temporomandibular clicking.…”
Section: Discussionmentioning
confidence: 52%
“…These results would agree with those obtained by Bakke et al [ 57 ], who, by BTX-A injections into the lateral pterygoid muscle, temporarily reduced the muscle action, but the clicking was permanently eliminated and did not reappear during the 1-year observation period, obtaining a small but clear positional improvement in the disc–condyle relationship. Similarly, other studies [ 58 , 59 , 60 ] with BTX-A injections into the lateral pterygoid muscle reported benefits on temporomandibular clicking.…”
Section: Discussionmentioning
confidence: 52%
“…An extraoral preauricular in-plane approach with ultrasound guidance can minimize the risk of complications 4,9 . Lower injection volume and dose are essential to reduce the risk of hemorrhage and complications due to proximity to vital structures when injecting BTX into the LP muscle 10 . Patients should receive proper medication and follow instructions, such as chewing bilaterally, eating soft foods, and using warm packs to alleviate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Joint click is mainly caused by DDWR and is a typical symptom for TMD [4]. ARS therapy is considered one of the most effective therapies for treating disc-displacement TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the ultimate goal of TMD manegement is to reduce or eliminate pain, to improve jaw function, and to enhance the quality of life [2,3]. As generally agreed, conservative treatments should always be the rst choice for TMD, including health education, medication, rehabilitation therapy, occlusal splint therapy, and even arthroscopic surgery [4].…”
Section: Introductionmentioning
confidence: 99%